Factors influencing group farmers’ behaviour towards safe pesticide use in Malaysia - Nyak Hashim, Nyak Nur Hamida; Mat Salleh, Roslina; Osman, Syuhaily; Md. Jusoh, Zuroni (Malaysian Consumer and Family Economics Association, 2020)
Pesticide is widely used by farmers to control agricultural pest. The purpose of this study was to measure factors influencing farmer’s safety behaviour in pesticide use. A total of 431 respondents from four states which are Perak, Pulau Pinang, Johor, and Kelantan were chosen through stratified random sampling. Multiple regression analysis found that attitude was the most influential factor for farmers’ behaviour with R square of 0.671. Farmers should have positive attitudes and obtain support from several parties to educate them to handle the pesticide wisely. This study provides several insights for policy makers to overcome the obstacle by providing farmers with technical guidance and designing long-term collaborative programmes that support, develop, and foster sense of control among farmers.